Encarceramento de mulheres na cadeia pública de Pato Branco - PR: interseccionalidade de gênero, raça e classe - Soldatelli, Brenda Debona (2020)
In this research I analyze the intersectionality of gender, race and class in the incarceration of women in the Public Prison of Pato Branco/PR. Inthe analysis, I present the emergence of modern prisons in the European context and the prisons in Brazil. I also address the history of women's imprisonment and their classification like a criminals. Furthermore, I demonstrate, from black and decolonialfeminism, how intersecctional inequalities were constituted, from the Eurocentric and colonial process of domination and control over women's bodies. Thus, I analyze how the intersectionality of gender, race and class operates in the incarceration of women. The research was carried out through a qualitative approach, based on the life history method of incarcerated women -through the technique of semi-structured interviews -and documentary analysis. The field research took place between 2018 and 2019. I found that the incarceration of women in the Pato Branco Public Jail is influenced more intensely by the axes of discrimination coming from gender and class, with race being a factor that operates with less intensity, due to the bleaching policy of the Southwest Paraná region in 20 century. I also found that the research participants are mothers and depend on relatives, especially their mothers, to take care of their daughters during their incarceration. The imprisonment of these women occurred, in the vastmajority of cases, for the crime of drug trafficking, which is motivated by the need to promote their own livelihood and that of their family. Finally, I observed that incarcerated women establish a set of relationships, which I called internal and external networks, which allow us to understand the reciprocity that they establish in the prison, intra and extra-prison contexts.